KAJIAN PERUBAHAN PENUTUPAN LAHAN PADA DAS CILIWUNG HULU DENGAN PENDEKATAN SPASIAL DINAMIK - Dedi Ruspendi; Setia Hadi; Omo Rusdiana (http://arl.faperta.ipb.ac.id/, 2013)
ABSTRACTLand cover changing that occurs in Ciliwung Upper Stream resulted increasing the water level in the main river. It is describe that environmental quality of the upstream has decreased. Based on toposequent, the damage in upstream will affect to middle and downstream of watershed. This study aims to analysis the pattern and distribution of land cover change and build Ciliwung Upper Stream model in spatial planning based on carrying capacity. The research was conducted in Ciliwung Upper Stream that located in Bogor region. The method was used in this study compare landcovering 1999 and 2010. This study results patterns and distribution of land coverchange then use as input to analysis of spatial dynamic. Analysis of the spatial dynamic results a good composition of land cover in the Ciliwung Upper Stream. Land cover composi-tion showed in table and spatial. Increasing of land cover has a high infiltration capac-ity can reduce the water level.Keyword: land cover changing, water level, spatial dynamic, watershed